2023
DOI: 10.1038/s41598-023-29077-y
|View full text |Cite
|
Sign up to set email alerts
|

Development of controlled nanosphere lithography technology

Abstract: This work is devoted to the development of nanosphere lithography (NSL) technology, which is a low-cost and efficient method to form nanostructures for nanoelectronics, as well as optoelectronic, plasmonic and photovoltaic applications. Creating a nanosphere mask by spin-coating is a promising, but not sufficiently studied method, requiring a large experimental base for different sizes of nanospheres. So, in this work, we investigated the influence of the technological parameters of NSL by spin-coating on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The proposed antenna is fabricated as seen in Fig. 8(a) using Nano sphere lithography and wet chemical etching processes that were used in [25]. The antenna structure is mounted on the Roger substrate to realize low dielectric material loss.…”
Section: Resultsmentioning
confidence: 99%
“…The proposed antenna is fabricated as seen in Fig. 8(a) using Nano sphere lithography and wet chemical etching processes that were used in [25]. The antenna structure is mounted on the Roger substrate to realize low dielectric material loss.…”
Section: Resultsmentioning
confidence: 99%
“…Natural lithography techniques have various benefits, such as the capacity to create ordered arrays, affordability, cost-efficiency, and compatibility with other lithography techniques. Nanosphere lithography is a form of natural lithography that employs colloidal nanospheres. This approach produces structures with a variety of applications, including photovoltaics, photocatalysis, and membranes for wastewater purification, as well as plasmonics for biosensing, surface-enhanced Raman scattering (SERS), plasmon-enhanced fluorescence, and solar water splitting. …”
Section: Introductionmentioning
confidence: 99%
“…Although these processes are suitable for laboratory-scale production, they are less useful for industrial processes due to the time scales and tedious fabrication processes involved. Past studies have demonstrated that the spin-coating process provides a simple and efficient method for the dispersion of small particles onto a substrate [16,17,[45][46][47][48][49][50][51][52][53].…”
Section: Introductionmentioning
confidence: 99%
“…Lan et al [46] synthesised silica nanocolloids of 196 nm diameter (standard deviation of ±40 nm) and fabricated close-packed colloidal monolayers that have shown promising properties for photonic and plasmonic nanostructures. More recently, Osipov et al [45] employed spin coating and 300 nm PS colloidal particles on silicon substrates to fabricate a high-quality and coverage monolayer close-packed colloidal coating, which was used as a colloidal mask to produce nanoneedles by plasma etching.…”
Section: Introductionmentioning
confidence: 99%